Safety and peaceful coexistence policies in Latin American schools: human rights perspective - Rodino, Ana María (2013)
The paper presents the theoretical framework, methodology and results of the X Inter-American Report on Human Rights Education, produced in 2011 by the Inter-American Institute for Human Rights (Costa Rica) under the coordination of the author. The research examines the increasing problem of securing peaceful coexistence, safety and prevention of school violence in 17 Latin American countries from South, Central and North America, and the educational policies they have developed or are currently developing to face it, analyzed from a human rights perspective.